Regular : the ultimate guide to taming unruly bowels and achieving inner peace - Freuman, Tamara Duker (Hachette Go, 2023)
"Belly bloat, diarrhea and constipation, and irritable bowels may not seem like the sexiest topics-but they still affect thousands of Americans every year. Rather than focusing on a single approach, Regular aims to help readers identify the likely cause of their irregular bowel symptoms with a wide variety of more personalized solutions. For example, Freuman explains that, while a high fiber diet that might help someone with opioid-induced constipation, it could make symptoms worse for someone constipated as the result of muscle dysfunction. Regular will guide readers to identify the specific cause of their irregularity and provide tips, including: questions to take to your next doctors visit; tables and charts listing foods likely to be problematic, and suggested alternatives; sample menus for different therapeutic diets; plus, foods and supplements that may be helpful for specific types of diarrhea and constipation. Whether you are dealing with chronic diarrhea or constipation, Regular will cover every condition that a sufferer might recognize, including: - Irritable Bowel Syndrome - Carbohydrate Intolerances - SIBO, Celiac Disease and Pancreatic Insufficiency - Inflammatory Bowel Disease (Crohn's disease and Ulcerative Colitis) - Pelvic Floor Dysfunction"--